PERAN PENDIDIKAN KEWARGANEGARAAN DALAM PENINGKATAN PERKEMBANGAN MORAL REMAJA - Qomariah, Amini Isti; Gustaman, Randy Fadillah; Rosita, Lilis (Jurnal Pengabdian Masyarakat Indonesia, 2024)
The role of civic education in improving morals of teenagers. As the development of the era, issues regarding moral decline in teenagers are increasingly common among society. Therefore, an education, especially civic education, needs to pay attention to its role in helping teenagers improve their morals in order to create the nation's next generation with morals and character in this modern era. In this journal, we will discuss the role of civic education in improving the moral development of teenagers in general. Through civic education it is hoped can be implemented by teenagers to improve their morality in the context of national and state life. As education that must be implemented, civic education is focused on forming the character of every citizen which is to be achieved in accordance with Pancasila as the state ideology. Through literature or literature study methods, this journal will describe the results of critical and in-depth analysis regarding the role of civic education in improving the morals of teenagers found in previous written works or research.